Structure-activity relationship of dibenzylideneacetone analogs against the neglected disease pathogen, Trypanosoma brucei - Francisco, Karol R.; Monti, Ludovica; Yang, Wenqian; Park, Hayoung; Liu, Lawrence J.; Watkins, Kaitlyn; Amarasinghe, Dilini K.; Nalli, Marianna; Roberto Polaquini, Carlos [UNESP]; Regasini, Luis O. [UNESP]; Eduardo Miller Crotti, Antônio; Silvestri, Romano; et al. (Elsevier, 2023)
Trypanosoma brucei is a protozoan parasite that causes Human African Trypanosomiasis (HAT), a neglected tropical disease (NTD) that is endemic in 36 countries in sub-Saharan Africa. Only a handful drugs are available for treatment, and these have limitations, including toxicity and drug resistance. Using the natural product, curcumin, as a starting point, several curcuminoids and related analogs were evaluated against bloodstream forms of T. b. brucei. A particular subset of dibenzylideneacetone (DBA) compounds exhibited potent in vitro antitrypanosomal activity with sub-micromolar EC50 values. A structure–activity relationship study including 26 DBA analogs was initiated, and several compounds exhibited EC50 values as low as 200 nM. Cytotoxicity counter screens in HEK293 cells identified several compounds having selectivity indices above 10. These data suggest that DBAs offer starting points for a new small molecule therapy of HAT.
Keywords: Antiparasitic activity; Curcuminoid; Cytotoxicity; Dibenzylideneacetone; Trypanosoma brucei